4CPS-162 Cytokine release syndrome in onco-haematological patients treated with tocilizumab. (23rd March 2022) - Molins, E; Mateo, E; Blazquiz, E; Serrano, M
Abstract : Background and importance: Cytokine release syndrome (CRS) is a common and life-threatening toxicity directly related to new targeted therapies for onco-haematological diseases. Although the optimal therapy for CRS remains unknown, tocilizumab has demonstrated success. Aim and objectives: To assess the efficacy of tocilizumab in onco-haematological patients with CRS. Relationship between CRS and targeted therapies was also reviewed. Material and methods: Retrospective cohort study in a single centre. Cases of onco-haematologic patients who received tocilizumab for CRS treatment from 2019 to 2021 were studied. Patient demographics, onco-haematological diagnosis and targeted therapy, CRS-related symptoms and tocilizumab treatment were collected from electronic patient files. CRS resolution after tocilizumab treatment was reviewed in order to evaluate the efficacy of therapy. CRS severity based on the American Society for Transplantation and Cellular Therapies grading scale for CRS was compared between the groups of patients with different onco-hamatologic diagnoses and targeted therapies. Results: A total of 47 patients received tocilizumab (46 hematologic and 1 oncologic) for CRS. Main onco-haematological diagnoses were multiple myeloma (75.5%), lymphoma (10.2%) and acute myeloblastic leukemia (8.2%). Targeted therapy consisted of c himeric antigen receptor T-cells (CAR-T-cells) in 29 patients (61.7%), bispecific antibodies in 16 (34.0%) and haematopoietic stem cell transplantation (HSCT) in 2 (4.3%). Nineteen patients (40.4%) developed CRS grade 1, 26 (55.3%) grade 2 and 2 (4.3%) grade 3. Tocilizumab median dose was 8.0 (5.3–10.4) mg/kg. Twelve patients (25.5%) required a second tocilizumab dose. CRS resolution occurred in all patients. CRS was more severe in the group of patients with a diagnosis of lymphoma, developing CRS grade 3 in 25% of patients versus 0% in the other groups (p<0.05). In the group of patients with multiple myeloma, CRS grade 1 occurred more frequently (48.5% vs 2.3%, p <0.05). Severe CRS (grade 2 and 3) was more frequent in patients treated with bispecific antibody or HSCT than in those who received CAR-T-cell therapy (77.8% vs 51.9%, p<0.05). Conclusion and relevance: Tocilizumab is an effective treatment in CRS after new targeted therapies in onco-haematological patients. Severity of CRS seems to be higher in patients with diagnosis of lymphoma and in those treated with bispecific antibodies and HSCT. References and/or acknowledgements: Conflict of interest: No conflict of interest